Cell Fusion-Related Proteins and Signaling Pathways, and Their Roles in the Development and Progression of Cancer - Zhang, Hao; Ma, Hong; Yang, Xiaohui; Fan, Linlin; Tian, Shifeng; Niu, Rui; Yan, Man; Zheng, Minying; Zhang, Shiwu (Frontiers in Cell and Developmental Biology, 2022)
Cell fusion is involved in many physiological and pathological processes, including gamete binding, and cancer development. The basic processes of cell fusion include membrane fusion, cytoplasmic mixing, and nuclear fusion. Cell fusion is regulated by different proteins and signaling pathways. Syncytin-1, syncytin-2, glial cell missing 1, galectin-1 and other proteins (annexins, myomaker, myomerger etc.) involved in cell fusion via the cyclic adenosine-dependent protein kinase A, mitogen-activated protein kinase, wingless/integrase-1, and c-Jun N-terminal kinase signaling pathways. In the progression of malignant tumors, cell fusion is essential during the organ-specific metastasis, epithelial-mesenchymal transformation, the formation of cancer stem cells (CSCs), cancer angiogenesis and cancer immunity. In addition, diploid cells can be induced to form polyploid giant cancer cells (PGCCs) via cell fusion under many kinds of stimuli, including cobalt chloride, chemotherapy, radiotherapy, and traditional Chinese medicine. PGCCs have CSC-like properties, and the daughter cells derived from PGCCs have a mesenchymal phenotype and exhibit strong migration, invasion, and proliferation abilities. Therefore, exploring the molecular mechanisms of cell fusion can enable us better understand the development of malignant tumors. In this review, the basic process of cell fusion and its significance in cancer is discussed.